N- terminal pro- B-type natriuretic peptide C- reactive protein and albumin as prognostic markers in severe sepsis and septic shock - Nesreen Farahat Soliman; Abeer Mosbah; Hatem Elatroush; Souzi Fawzi (Cairo : Nesreen Farahat Soliman, 2013)
objective : N-terminal pro-BNP (NTproBNP) could be useful to predict outcome in severe sepsis and septic shock . We have conducted a study to evaluate NTproBNP CRP and serum albumin levels in the setting of severe sepsis or septic shock . Conelusions : NT-proBNP values are frequently increased in severe sepsis and septic shock . Values are sigificantly higher in nonsurvivors than survivors
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Critical Care Medicine
Issued also as CD
Keywords: Mortality; Septic shock; Severe sepsis